Heterologous Materials Are Really Better than Autologous in Tympanoplasty Mastoid Obliteration? A Systematic Review with Meta-Analysis - Francesca Viberti; Giovanni Monciatti; Aniello Donniacuo; Fabio Ferretti; Lorenzo Salerni; Andrea De Vito; Daniele Bernardeschi; Marco Mandalà (Journal of International Advanced Otology)
Background: The aim is to analyze Literature concerning mastoid obliteration in adults with either autologous or heterologous grafts in the last 10 years. Data Source: Databases such as NIH PubMed, Bookshelf, NLM Catalog, Cochrane Library, and Embase were consulted.